2019
DOI: 10.1002/cncy.22203
|View full text |Cite
|
Sign up to set email alerts
|

Plasma‐thrombin cell blocks: Potential source of DNA contamination

Abstract: Background Cell blocks are being used more frequently in cytology for ancillary testing, including molecular diagnostics. There are several different methods of processing cell blocks, with plasma‐thrombin being one of the most common. Plasma is a blood‐derived product and may be a source of DNA. The aim of this study was to determine whether the plasma used for the plasma‐thrombin cell block method has amplifiable DNA that may potentially interfere with molecular testing results. Methods Expired bags of fresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…However, the fibrin could be seen in the PT method just as other studies have reported 20 . One study demonstrated the presence of significant amounts of amplifiable DNA in expired plasma, which can potentially contaminate CB samples prepared with PT 14 . Theoretically, cell‐free DNA and circulating tumor DNA may interfere with molecular tests.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the fibrin could be seen in the PT method just as other studies have reported 20 . One study demonstrated the presence of significant amounts of amplifiable DNA in expired plasma, which can potentially contaminate CB samples prepared with PT 14 . Theoretically, cell‐free DNA and circulating tumor DNA may interfere with molecular tests.…”
Section: Discussionmentioning
confidence: 99%
“…20 One study demonstrated the presence of significant amounts of amplifiable DNA in expired plasma, which can potentially contaminate CB samples prepared with PT. 14 Theoretically, cell-free DNA and circulating tumor DNA may interfere with molecular tests. Therefore, further analysis of the safety of the PT method for molecular tests using CBs is needed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, plasma contains cell-free DNA, 10 which might be a source of DNA contamination and can lead to a false-positive or false-negative results of molecular analysis. 11 Moreover, thrombin reagents might contain contaminant extraneous cells, 7 and this could also interfere with the results of molecular or immunocytochemical analysis. 7,10 Second, sources of plasma and thrombin are not standardized and vary not only between laboratories but also in each individual laboratory over time.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are several reasons why this method should no longer be used in a modern cytology practice. First, plasma contains cell‐free DNA, 10 which might be a source of DNA contamination and can lead to a false‐positive or false‐negative results of molecular analysis 11 . Moreover, thrombin reagents might contain contaminant extraneous cells, 7 and this could also interfere with the results of molecular or immunocytochemical analysis 7,10 .…”
Section: Discussionmentioning
confidence: 99%